EFEKTIVITAS TERAPI FOOT MASSAGE DAN AROMATERAPI LAVENDER TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI - Saputra, Wahyudi; Husni, Husni; Septiyanti, Septiyanti; Buston, Erni (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, 2025)
Hypertension is a silent disease or an unknown disease. Epidemiological data have shown that adults aged 18 years have a higher risk of developing hypertension. The prevalence of hypertension in Bengkulu is quite high. Data from the Bengkulu City Health Office recorded that 36,404 people were diagnosed with hypertension. This study aimed to determine the effect of foot massage and lavender aromatherapy on blood pressure in hypertensive patients. This research type was quantitative research using a quasi-experimental design using a post-test and pre-test with control group design with sample size of 36 people, divided into 2 groups. Sample selection used a purposive sampling technique where respondents were taken based on inclusion criteria which included age between 18-50 years, systolic blood pressure ≥140 mmHg, and diastolic ≥90 mmHg. The tool used a digital blood pressure measuring device whose validity has been tested. The calibration carried out is comparing the first and second blood pressure using an Omicron blood pressure measuring instrument. The reliability test was carried out by measuring blood pressure 2 times. The results of the study showed that there was a difference in average systolic and diastolic blood pressure between the intervention group and the control group. Statistical tests using the Independent T-test method showed p-value of 0.001 (p-value ≤α 0.05), which shows the influence of foot massage and lavender aromatherapy on blood pressure in hypertension sufferers. It is estimated that hypertension sufferers can apply independent interventions that have been taught so that blood pressure can be controlled.